2011
DOI: 10.21273/horttech.21.5.546
|View full text |Cite
|
Sign up to set email alerts
|

Crop Load Management Does Not Consistently Improve Crop Value of ‘Sweetheart’/‘Mazzard’ Sweet Cherry Trees

Abstract: The effect of crop load level on vegetative growth, fruit growth, yield, fruit quality, surface pitting, crop value and return bloom was studied over a 2-year period on 9- and 10-year-old ‘Sweetheart’/‘Mazzard’ sweet cherry (Prunus avium) trees. In early spring, whole-tree crop loads were adjusted to two different levels by removal of reproductive buds (either 50% or all but one) from spurs and compared with an unthinned control. In 2009, heavy crop loads of unthinned trees r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
6
14
0
Order By: Relevance
“…Lenahan et al (2006) concluded that GA 3 and GA 4/7 were ineffective at producing balanced croploads of 'Bing' the subsequent season; GA 4/7 having a greater effect than GA 3 . We hypothesized that high rates of GA 3 may improve crop value for 'Sweetheart' and 'Lapins' given these genotypes' inherently high productivity, a trait that promotes ''oversetting,'' particularly for 'Sweetheart' (Einhorn et al, 2011). In our study, lower return bloom was attributed to fewer flowers per floral bud and not the result of a reduction in the number of reproductive buds per spur, as similarly observed for 'Bing' (Facteau et al, 1989;Lenahan et al, 2006).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Lenahan et al (2006) concluded that GA 3 and GA 4/7 were ineffective at producing balanced croploads of 'Bing' the subsequent season; GA 4/7 having a greater effect than GA 3 . We hypothesized that high rates of GA 3 may improve crop value for 'Sweetheart' and 'Lapins' given these genotypes' inherently high productivity, a trait that promotes ''oversetting,'' particularly for 'Sweetheart' (Einhorn et al, 2011). In our study, lower return bloom was attributed to fewer flowers per floral bud and not the result of a reduction in the number of reproductive buds per spur, as similarly observed for 'Bing' (Facteau et al, 1989;Lenahan et al, 2006).…”
Section: Discussionsupporting
confidence: 59%
“…Although high rates of GA 3 have been investigated as a cropload management strategy for 'Bing' the season after application (Lenahan et al, 2006;Proebsting and Mills, 1974), significantly lower return bloom severely reduced crop value when different isomers of GA (GA 3 or GA 4/7 ) were applied at 100 and 200 ppm (Lenahan et al, 2006). 'Bing', however, is not regarded as a highly productive variety, unlike several of the selffertile, precocious, and productive late-season cultivars that produce a large proportion of undersized fruit of poor quality during high cropload years (Einhorn et al, 2011). Potentially, different cultivars may respond differently to high rates of GA 3 .…”
mentioning
confidence: 99%
“…It is not possible to determine conclusively from our data if these year-to-year differences in fruit quality are primarily the result of variation in cropload or other factors acting independently on both, but the depressive effect of high fruit load on cherry SSC has been previously reported (Marsal et al, 2010). Einhorn et al (2011) found in controlled thinning experiments over two growing seasons that average fruit size, SSC, firmness, and TA were increased on 'Sweetheart' sweet cherry on Mazzard rootstock on thinned trees with low cropload. Our results further suggest that high cropload can decrease fruit TA and firmness indicating that differences in fruit quality related to cultivars may be altered by differences in cropload.…”
Section: Resultsmentioning
confidence: 67%
“…The greater SSC observed in a limited sample of fruit from infected plants is consistent with what might be expected in plants with reduced water uptake because of plugging of the xylem. Also, studies involving other fruit crops have sometimes shown that greater SSCs were associated with reduced crop loads (Berkey et al, 2011;Einhorn et al, 2011;Serra et al, 2016). Researchers should be aware of a possible effect of X. fastidiosa in case unexplained variations in soluble solids are observed, for example, in a cultivar or breeding line evaluation of a plant species in which X. fastidiosa can be a chronic issue (P. Perkins-Veazie, personal communication).…”
Section: Discussionmentioning
confidence: 99%